Humanized Anti-CD19 CAR-T Cell Therapy and Sequential Allogeneic Hematopoietic Stem Cell Transplantation Achieved Long-Term Survival in Refractory and Relapsed B Lymphocytic Leukemia: A Retrospective Study of CAR-T Cell Therapy - Chen, Wei; Ma, Yuhan; Shen, Ziyuan; Chen, Huimin; Ma, Ruixue; Yan, Dongmei; Shi, Ming; Wang, Xiangmin; Song, Xuguang; Sun, Cai; Cao, Jiang; Cheng, Hai; et al. (Frontiers in Immunology, 2021)
Early response could be obtained in most patients with relapsed or refractory B cell lymphoblastic leukemia (R/R B-ALL) treated with chimeric antigen receptor T-cell (CAR-T) therapy, but relapse occurs in some patients. There is no consensus on treatment strategy post CAR-T cell therapy. In this retrospective study of humanized CD19-targeted CAR-T cell (hCART19s) therapy for R/R B-ALL, we analyzed the patients treated with allogeneic hematopoietic stem cell transplantation (allo-HSCT) or received a second hCART19s infusion, and summarized their efficacy and safety. We retrospectively studied 28 R/R B-ALL patients treated with hCART19s in the Affiliated Hospital of Xuzhou Medical University from 2016 to 2020. After the first hCART19s infusion, 10 patients received allo-HSCT (CART+HSCT group), 7 patients received a second hCART19s infusion (CART2 group), and 11 patients did not receive HSCT or a second hCART19s infusion (CART1 group). The safety, efficacy, and long-term survival were analyzed. Of the 28 patients who received hCART19s treatment, 1 patient could not be evaluated for efficacy, and 25 (92.6%) achieved complete remission (CR) with 20 (74.7%) achieving minimal residual disease (MRD) negativity. Seven (25%) patients experienced grade 3-4 CRS, and one died from grade 5 CRS. No patient experienced ≥3 grade ICANS. The incidence of second CR is higher in the CART+HSCT group compared to the CART2 group (100% vs. 42.9%, p=0.015). The median follow-up time was 1,240 days (range: 709–1,770). Significantly longer overall survival (OS) and leukemia-free survival (LFS) were achieved in the CART+HSCT group (median OS and LFS: not reached, p=0.006 and 0.001, respectively) compared to the CART2 group (median OS: 482; median LFS: 189) and the CART1 group (median OS: 236; median LFS: 35). In the CART+HSCT group, the incidence of acute graft-versus-host disease (aGVHD) was 30% (3/10), and transplantation-related mortality was 30% (3/10). No chronic GVHD occurred. Multivariate analysis results showed that blasts ≥ 20% in the bone marrow and MRD ≥ 65.6% are independent factors for inferior OS and LFS, respectively, while receiving allo-HSCT is an independent factor associated with both longer OS and LFS. In conclusion, early allo-HSCT after CAR-T therapy can achieve long-term efficacy, and the adverse events are controllable.